Reduction of Saturated Alkyl Halides to Alkanes - Ziffle, V; Fletcher, S (Elsevier, 2014)
This chapter describes the hydrogenolysis of a saturated halide (I, Br, Cl, and F) to an alkane. A number of methods have been developed for these reductions, and the ones that are thought to be the most useful are described here. The methods are assessed by the type of reagent that is being used to carry out the transformation, with the emphasis being placed on reliable methods that are chemoselective and generally applicable. References to reviews are provided to facilitate an indepth view of a particular reaction types and their uses. © 2014 Elsevier Ltd. All rights reserved.